2022
DOI: 10.1002/mp.15649
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high dose rate dosimetry: Challenges and opportunities for FLASH radiation therapy

Abstract: The clinical translation of FLASH radiotherapy (RT) requires challenges related to dosimetry and beam monitoring of ultra‐high dose rate (UHDR) beams to be addressed. Detectors currently in use suffer from saturation effects under UHDR regimes, requiring the introduction of correction factors. There is significant interest from the scientific community to identify the most reliable solutions and suitable experimental approaches for UHDR dosimetry. This interest is manifested through the increasing number of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 165 publications
1
115
0
Order By: Relevance
“… 11 However, BCTs have two main limitations relative to traditional transmission chambers: (1) their inability to monitor the beam's spatial profile (flatness and symmetry) and (2) their utility in monitoring the beam is limited to charged particles only. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 11 However, BCTs have two main limitations relative to traditional transmission chambers: (1) their inability to monitor the beam's spatial profile (flatness and symmetry) and (2) their utility in monitoring the beam is limited to charged particles only. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Dosimetry at UHDR is complicated and it is essential to understand the effects that impact detector response in this radiotherapy modality. An extensive review on detectors used in UHDR beams can be found in 25 . The use of a Faraday cup for the commission of a beam monitor at UHDR has been reported 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment described in this work, an SiC membrane sensor was used, produced by the SenSiC company [ 10 ]. SiC membranes have recently demonstrated promising hard X-ray beam position monitoring capabilities [ 11 ], as well as promising ultra-high-dose-rate electron beam dosimetry monitoring capabilities, in the so-called Flash Radiotherapy application [ 12 , 13 ]. These devices are semiconductor PiN junctions: they are composed of a thin, 0.3 m p highly doped ( cm ) layer and a 20 m n low-doped ( cm ) layer on top of a ∼370 m thick n ( cm ) substrate.…”
Section: Methodsmentioning
confidence: 99%